Content optimization of the development of multiproject of a shipping company - Lapkina, Inna; Prykhno, Yuliya; Lapkin, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2020)
An economic-mathematical model of content optimization of the development multi-project of the project-oriented enterprise in a general form is proposed. The developed economic-mathematical model of multi-project content optimization allows creating a development multi-project taking into account the specifics of the activity, resources and capabilities of the company. It is shown that the current situation requires new methods in managing problem areas of the economy. The issue of attracting and distributing resources is particularly relevant for shipping companies. The economic-mathematical model of content optimization of the development multi-project of a shipping company is experimentally investigated. It is shown that the connection between projects in the development multi-project of the shipping enterprise is implemented through resources and strategic goals. The connections between development projects are investigated. The relationship between projects within the framework of the development multi-project of the shipping company in such areas as: resource restrictions, restrictions at the level of goals, restrictions at the organization level is considered. The presented economic-mathematical model of content optimization of the development multi-project of the shipping company allows determining strategic goals in the long period, evaluating the resources needed to achieve them, and determining the sources of their replenishment. The economic-mathematical model makes it possible to take into account not only resource limitations, but also the compliance of the results of the multi-project with the strategic goals of the company. The optimal content of the development multi-project of the shipping company is obtained for a given level of the company’s ability to finance projects in the current period; and the company’s ability to finance projects as part of the multi-project throughout the entire life cycle. The presented approach to the formation of the development multi-project of the shipping company allows achieving the strategic goals of the company in the unity of the project, multi-project and portfolio of the enterprise